The role of anxiety in patients with hereditary angioedema during oral treatment: a narrative review - Rosa, Alessio; Franco, Rocco; Miranda, Michele; Casella, Sergio; D’Amico, Cesare; Fiorillo, Luca; Cervino, Gabriele (Frontiers in Oral Health, 2023)
Objective The present study investigated the clinical potential of managing anxiety during dental procedures to reduce acute attacks in patients with hereditary angioedema (HAE). HAE is a rare disease, little known to physicians and dentists, but with an increased hospitalization rate over the years. HAE is due to a deficiency/dysfunction of the C1 esterase inhibitor, leading to increased vascular permeability. Recommendations for HAE management include long-term and short-term prophylaxis and treatment of acute attacks, but the importance of anxiety control is underestimated. Materials and methods The authors reviewed the literature to provide the scientific community with an overview of possible protocols for managing anxiety in dental practice and their effectiveness. Management can be used in prosthetics, periodontal and implant surgery, endodontics, and oral surgery. Discussions Our analysis shows that although there are few articles in the indexed literature, protocols for managing anxiety in HAE patients in dentistry will become increasingly prevalent in the daily clinical practice of dentists due to its benefits. Conclusions The benefits and better control of intraoperative complications and risks may lead clinicians to use sedation, assessment, or anxiety control techniques in daily clinical practice to reduce such attacks. Clinical relevance: This study suggests that controlling and managing anxiety can help prevent and reduce acute angioedema attacks.